Prevention, rehabilitation and preparation (Handball Sports Medicine, 2018)
Injury Prevention in Handball (G. Myklebust, M. K. Zebis, S. H. Andersson) 403-412 Implementing Handball Injury Prevention Exercise Programs: A Practical Guideline (M. Møller, E. Ageberg, J. Bencke, M. K. Zebis, G. Myklebust) 413-432 Rehabilitation of Upper Extremity Injuries in the Handball Player (A. Cools, R. Whiteley, P. K. Kaczmarek) 433-459 Shoulder Assessment in Handball Players (M. Asker, R. Whitley, A. Cools) 461-480 Rehabilitation of ACL Injury in the Handball Player (C. Ardern, H. Grindem, J. Kvist, M. Waldén, M. Hägglund) 481-491 A Biomechanical Perspective on Rehabilitation of ACL Injuries in Handball (I. Setuain, J. Bencke, J. Alfaro-Adrián, M. Izquierdo) 493-504 Rehabilitation of Acute Soft Tissue Injuries of the Foot and Ankle in the Handball Player (M. Hägglund, H. Pereira, M. Carmont, J. Karlsson, P. D`Hooghe) 505-519 Physical Training in Team Handball (A. Dello Iacono, C. Karcher, L. Bojsen Michalsik) 521-535 Stretch-Shortening Cycle Exercises in Young Elite Handball Players: Empirical Findings for Performance Improvement, Injury Prevention, and Practical Recommendations (U. Granacher, R. Goebel, D. G. Behm, D. Büsch) 537-550